Deletion of Metabotropic Glutamate Receptors 2 and 3 (mGlu2 & mGlu3) in Mice Disrupts Sleep and Wheel-Running Activity, and Increases the Sensitivity of the Circadian System to Light. - David Pritchett; Aarti Jagannath; Laurence A Brown; Shu K E Tam; Sibah Hasan; Silvia Gatti; Paul J Harrison; David M Bannerman; Russell G Foster; Stuart N Peirson (PLoS ONE)
Sleep and/or circadian rhythm disruption (SCRD) is seen in up to 80% of schizophrenia patients. The co-morbidity of schizophrenia and SCRD may in part stem from dysfunction in common brain mechanisms, which include the glutamate system, and in particular, the group II metabotropic glutamate receptors mGlu2 and mGlu3 (encoded by the genes Grm2 and Grm3). These receptors are relevant to the pathophysiology and potential treatment of schizophrenia, and have also been implicated in sleep and circadian function. In the present study, we characterised the sleep and circadian rhythms of Grm2/3 double knockout (Grm2/3-/-) mice, to provide further evidence for the involvement of group II metabotropic glutamate receptors in the regulation of sleep and circadian rhythms. We report several novel findings. Firstly, Grm2/3-/- mice demonstrated a decrease in immobility-determined sleep time and an increase in immobility-determined sleep fragmentation. Secondly, Grm2/3-/- mice showed heightened sensitivity to the circadian effects of light, manifested as increased period lengthening in constant light, and greater phase delays in response to nocturnal light pulses. Greater light-induced phase delays were also exhibited by wildtype C57Bl/6J mice following administration of the mGlu2/3 negative allosteric modulator RO4432717. These results confirm the involvement of group II metabotropic glutamate receptors in photic entrainment and sleep regulation pathways. Finally, the diurnal wheel-running rhythms of Grm2/3-/- mice were perturbed under a standard light/dark cycle, but their diurnal rest-activity rhythms were unaltered in cages lacking running wheels, as determined with passive infrared motion detectors. Hence, when assessing the diurnal rest-activity rhythms of mice, the choice of assay can have a major bearing on the results obtained.